2008
DOI: 10.1007/s11858-008-0132-x
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetics as a liberating force in mathematics education?

Abstract: This article investigates different meanings associated with contemporary scholarship on the aesthetic dimension of inquiry and experience, and uses them to suggest possibilities for challenging widely held beliefs about the elitist and/or frivolous nature of aesthetic concerns in mathematics education. By relating aesthetics to emerging areas of interest in mathematics education such as affect, embodiment and enculturation, as well as to issues of power and discourse, this article argues for aesthetic awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
0
27
0
2
Order By: Relevance
“…Instead, the question under consideration is why this sequence was aesthetically compelling to these students in this context. Certainly, aesthetic experiences vary by individual [18] and the meaning generated during a story is a mixture of a reader's goals, experience, and purpose, and thus is individual in nature [15]. Since the audience of the enacted mathematical story described earlier was arguably the students, I maintain that the students' evaluation of the experience is the appropriate measure of its aesthetic value.…”
Section: The Lesson As a Mathematical Storymentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the question under consideration is why this sequence was aesthetically compelling to these students in this context. Certainly, aesthetic experiences vary by individual [18] and the meaning generated during a story is a mixture of a reader's goals, experience, and purpose, and thus is individual in nature [15]. Since the audience of the enacted mathematical story described earlier was arguably the students, I maintain that the students' evaluation of the experience is the appropriate measure of its aesthetic value.…”
Section: The Lesson As a Mathematical Storymentioning
confidence: 99%
“…After this, I discuss the role of sequence with regard to how the students came to this aesthetic moment and also explore what might have changed if the sequence were altered. Finally, I end with a discussion of mathematical beauty, drawing connections and distinctions with other theories, stories, and analyses (e.g., [4,11,12,14,18,19]). …”
mentioning
confidence: 99%
“…From a theoretical standpoint, the case of interest is situated at the crossroad of two general perspectives for conceptualizing mathematical beauty, objectivism and subjectivism, the latter also referred to as projectivism [6,36]. From the perspective of objectivism, mathematical beauty is an intrinsic property of a problem, theorem, or proof, and is consequently independent of the observer and the socio-historical context surrounding it [6].…”
Section: Conceptualization Of Mathematical Beautymentioning
confidence: 99%
“…Clarifying this approach is McAllister [24], who regards beauty as "a value that is projected into or attributed to objects by observers, not a property that intrinsically resides in objects" (page 15). Under this approach, what is considered to be mathematically beautiful is influenced by personal taste, previous personal knowledge and experience, age of the observer, and socio-historical cultural context (compiled from [3,9,31,34,36,38]). From an educational point of view, empirical research has shown evidence that students do in fact hold aesthetic sensibilities for mathematics, though their aesthetic views and judgments often differ from those of mathematicians, possibly as a result of different personal and psychological needs [3,4,19,35].…”
Section: Conceptualization Of Mathematical Beautymentioning
confidence: 99%
See 1 more Smart Citation